KEGIATAN SOSIALISASI PENGENALAN MARKETING SECARA DIGITAL BERSAMA TOKO KERUPUK DAN KEMPLANG 770 - Wijaya, Andrian; Hartanti, Ery; Feriyanto; Wijaya, Laurentius Ricardo; Vincent (Politeknik Negeri Sriwijaya, 2024)
This community service activity aimed to introduce digital marketing to the employees of Toko Kerupuk dan Kemplang 770. The approach involved delivering educational materials on digital marketing and training on creating poster designs for marketing purposes. Conducted on April 21, 2024, the activity successfully helped employees understand and apply the concepts of digital marketing. The main advantage was the enhancement of employees' knowledge and skills in digital marketing, although the attendance was not optimal, affecting the overall effectiveness of the training. This initiative is expected to assist the store in attracting more customers through improved marketing strategies.